2022
DOI: 10.1186/s12889-022-13521-1
|View full text |Cite
|
Sign up to set email alerts
|

eHealth usage among Chinese college students: qualitative findings

Abstract: Background The information technology has developed rapidly with the evolution of internet environment transformed from requiring computer skills for information searching to self-managing health data and applying information. Therefore, a more diverse range of eHealth skills is required and these skills are referred as eHealth literacy. However, most eHealth literacy studies focused mainly on information searching skills. Little is known about eHealth usage behaviors of college students in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…One likely reason is that older adults rarely have the expertise to use DHT appropriately, and web-based misinformation causes older adults to distrust DHT to some extent [ 31 ]. This distrust may prevent users from using DHT more frequently [ 32 ]. It may be difficult for older adults to tell to what extent DHT is useful or easy to use if they use DHT superficially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One likely reason is that older adults rarely have the expertise to use DHT appropriately, and web-based misinformation causes older adults to distrust DHT to some extent [ 31 ]. This distrust may prevent users from using DHT more frequently [ 32 ]. It may be difficult for older adults to tell to what extent DHT is useful or easy to use if they use DHT superficially.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis also showed that eHealth literacy was significantly connected with all the variables except discomfort and insecurity. This might be because the current measurement for eHealth literacy is developed on the basis of Web 1.0 technology, which is a web-based environment, while new technologies (eg, social networking services or mobile internet) have been applied in current DHT [ 32 ]. In that case, older adults may still be confused by new DHT and perceived discomfort and insecurity, even if they know how to obtain information from health-related websites.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is becoming a pervasive public health problem that has been associated with unhealthy behaviors, such as lack of physical activity, smoking, and poor diet, subsequently leading to an increased risk of health problems, even among healthy individuals ( Bonnet et al, 2005 ). College students are among the most affected groups of people due to their potentially having to manage their stress, anger, or frustration on their own for the first time ( Liu et al, 2022 ). They must not only face various problems in their studies, work, and feelings but also solve problems of interpersonal communication.…”
Section: Introductionmentioning
confidence: 99%
“…time (Liu et al, 2022). They must not only face various problems in their studies, work, and feelings but also solve problems of interpersonal communication.…”
mentioning
confidence: 99%
“…In a qualitative study, Chinese college students perceived eHealth tools as convenient in health self-management and usually used them to monitor their own health. In particular, medical major college students actively accessed online health information as references to solve their health problems [ 22 ]. However, there is a notable risk of exposure to unreliable health information, a difficulty in identifying the correct information available online, or misuse of health information, which result in adverse effects such as anxiety [ 23 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%